The challenge of choosing in cardiovascular risk management - Hoogeveen, R. M.; Hanssen, N. M. J.; Brouwer, J. R.; Mosterd, A.; Tack, C. J.; Kroon, A. A.; de Borst, G. J.; ten Berg, J.; van Trier, T.; van Lennep, J. Roeters; Liem, A.; Serné, E.; et al. (Netherlands heart journal, 2022)
Cardiovascular disease (CVD) is a major cause of morbidity and mortality worldwide. For many years guidelines have listed optimal preventive therapy. More recently, novel therapeutic options have broadened the options for state-of-the-art CV risk management (CVRM). In the majority of patients with CVD, risk lowering can be achieved by utilising standard preventive medication combined with lifestyle modifications. In a minority of patients, add-on therapies should be considered to further reduce the large residual CV risk. However, the choice of which drug combination to prescribe and in which patients has become increasingly complicated, and is dependent on both the absolute CV risk and the reason for the high risk. In this review, we discuss therapeutic decisions in CVRM, focusing on (1) the absolute CV risk of the patient and (2) the pros and cons of novel treatment options.